RESISTANCE OF PHASEOLUS VULGARIS L. ACCESSIONS TO RACES 2 AND 7 OF COLLETOTRICHUM LINDEMUTHIANUM AS A BASIS FOR AGROBIODIVERSITY CONSERVATION (Eurasian Journal of Ecology, 2026)
The common bean (Phaseolus vulgaris L.) is an important grain legume crop with high nutritional, economic and genetic value. Anthracnose, caused by Colletotrichum lindemuthianum, is one of the most destructive diseases of this crop, and the high race variability of the pathogen complicates the selection of resistant breeding material. The aim of this study was to evaluate the resistance of 10 bean accessions and 2 control samples to races 2 and 7 of C. lindemuthianum under greenhouse conditions. The scientific and practical significance of the work lies in identifying accessions suitable for breeding, hybridisation and the conservation of bean agrobiodiversity. Seeds provided by Michigan State University were used, while MDRK and MICH served as control samples. Inoculation was carried out separately for each pathogen race, and the degree of plant infection was assessed visually using the CIAT 1–9 rating scale. The results showed that most of the tested accessions demonstrated resistance to anthracnose; the control samples MDRK and MICH were susceptible, whereas Beluga showed only mild symptoms. The value of the study is that it confirms the importance of multi-race screening in phytopathological evaluation. The practical significance of the results is the selection of resistant genotypes for further breeding work. Keywords: Common bean, anthracnose, Colletotrichum lindemuthianum, resistance, agrobiodiversity.